Studying the thermal condition of an automated 6 (10) Kv electric power fiscal metering location - E. E. Gotovkina; A. A. Yablokov; N. N. Smirnov; A. V. Panashatenko; V. D. Lebedev; O. A. Dobryagina (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Examine the problem of reliable functioning of small electric power fiscal metering locations (EPFML) based on unconventional instrument current and voltage converters (Rogowski coil and resistive divider). Identify the most severe environmental conditions in which EPFML can be operated. Conduct research into EPFML thermal condition in different grid operation modes, and also during high voltage testing. Determine the conditions in which heat emission at the resistor divider attains its maximum value. METHODS. To solve the problem, use was made of three-dimensional hybrid field and chain simulation models, calculated by the methods of finite elements and linear electric circuit theory. The developed simulation models enable research to be conducted not only in normal, but also emergency electric grid operation, during lightning and pulse surges, insulation testing, and in the presence of insolation. RESULTS. The article presents the results of research concerning the thermal condition of a 6 (10) kV automated electric power fiscal metering location. CONCLUSION. If a resistive divider is used as a primary voltage converter, maximum heat emission occurs in the event of intermittent single phase arc faults to earth in accordance with Petersen’s theory. The results of the conducted research show that an EPFML based on a resistive voltage divider should be calculated using simulated models, taking into account insolation and the daily pattern of changes in maximum ambient temperature.